Manajemen Strategi Berbasis SWOT (Strength, Weakness, Opportunity, Dan Threat) dalam Perencanaan dan Pengembangan Sumber Daya Manusia pada PT ABC - Sitanggang, Antonius Nathanael; Sumiati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
PT ABC is a state-owned company engaged in international and domestic container handling services based in Surabaya, East Java. In improving service quality, especially in improving container flow, PT ABC conducts human resource planning and development, which is one of the important factors. This study analyses the factors that influence human resource planning and development in order to achieve optimal strategic management. The method used for strategic management is the SWOT method (Strength, Weakness, Opportunity, and Threat). This research was conducted through field observations, interviews and the distribution of questionnaires to employees involved in human resource planning and development. The research results show that the calculations of the Internal Factor Strategy Analysis and External Factor Strategy Analysis matrices indicate that the values obtained are 0.15 and 0.17 respectively, which places PT ABC's factors in Quadrant I, indicating that the strengths and opportunities are the strongest factors in strategy determination. Therefore, the strategy implemented is an aggressive or expansionary strategy.